POLA KOMUNIKASI ANAK AUTIS DI DALAM KELUARGA - Ade Yolanda Putra Septian; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is titled “Communication Patterns Of Autistic Childern In The Family”. This research is spreading the lives of the children of Autis who do all their activities with different communication patterns with the child in general in carrying out roles in his life. Being an autistic child or as the center of attention in the family, does not make a burden for families who have autistic children in their families. The methods used in this research are the research methods. Qualitative descriptive, that is, discusses this research presented as well as analyzed in the form of descriptions of words (descriptive) with a qualitative approach. In addition, this research is also supported by the implementation of an interview activity in depth to the informant (informant) that has been established by the researchers first. From the results of the interview, it is obtained a very supportive information for the validity of the data that is the focus of research. Based on the results of the study, the children of Autis run their activities with different communication patterns with the children in general. However, in the attitude of autistic children who have similarities and differences when communicating with their opponents. In addition to this autistic child also expects the role of the family as a nearby person when he or she wants to communicate or misplace when his autistic child is interacting as a means of communication in his personal life. Keywords: Communication Pattern, Autistic, Family